Reading Surah Ar-Rahman to Reduces Blood Pressure Among Hypertension Patients - Fitri, Jasrita; Apriadi, Dwi (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: Increased blood pressure in the long term can cause coronary heart disease, kidney damage and stroke. Indonesia is one of the developing countries that has the highest prevalence of hypertension and the 5th most killer disease. One of the non-pharmacological nursing interventions that can be applied to hypertensive patients is reading the Qur'an. Surah Ar-Rahman can be used as an alternative non-pharmacological treatment for people with hypertension.Purpose: this study was to determine the effect of reading Surah Ar-Rahman on blood pressure in patients with hypertension.Method: This type of quantitative research used a quasi-experiment with a two- group pre-test-post-test with control group design. Results: the sample in this study was 46 respondents, the sampling technique was purposive sampling and the data collection used an observation form. The bivariate test using Wilcoxcon.Result: the results of the study found that the average systolic blood pressure before therapy for reading Surah Ar-Rahman was 155.65 mmHg and the diastolic was 95.22 mmHg and the average systolic blood pressure after the intervention was reading Surah Ar-Rahman. Rahman is 145.22 mmHg and his diastolic is 89.57 mmHg. Thus the Wilcoxon Test results obtained statistical results obtained systolic p value = 0.000 and diastolic p value = 0.003 (p < 0.05) which means there is a significant change in blood pressure reduction in hypertensive patients who have been given therapy reading Surah Ar-Rahman.Conclusion: the recommendation for nurses to be used as a basis for realizing evidence-based practice in the treatment of hypertension sufferers with complementary therapies.